Agricultural policy reform : politics and process in the EU and US in the 1990s - Moyer, H. Wayne; Josling, Tim, 1940- (Aldershot, Hants, England ; Burlington, VT : Ashgate, 2002)
An analysis of domestic policy reform in the US and the EU, agricultural trade policy reform in the GATT/WTO, the interplay between US and EU reforms and the linkage between domestic and trade policy reform. It explains why reforms in the US and EU took parallel courses during the 1990s.
Sequel to: The politics of agricultural reform in the United States and the European Community.
Includes bibliographical references and index.
oif 15/09/15
Loan
Keywords: Agriculture and state -- United States; Agricultural price supports -- United States; Produce trade -- Government policy -- United States; Agriculture and state -- European Economic Community countries; Agricultural price supports -- European Economic Community countries; Produce trade -- Government policy -- European Union countries